1983
DOI: 10.1111/j.1423-0410.1983.tb01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HBsAg Subtypes in the World

Abstract: HBsAg subtyping was performed in 5,337 sera from chronic carriers who originated from 54 different countries of the 5 continents. Nine subtypes were defined: ayw1, ayw2, ayw3, ayw4, ayr, adw2, adw4, adr q- and adr q+. The repartition of these subtypes, according to the country of origin of the carriers, enhances the previous results and supplies new data: ayw1 is prevalent only in Vietnam (51%); ayw2 in Mediterranean countries (73%); ayw3 in Greece and Yugoslavia (54%) along with ayw2 (41%); ayw4 in West Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(89 citation statements)
references
References 23 publications
9
79
1
Order By: Relevance
“…Size differences between the HBV DNA fragments amplified from the sera and those from the plasmids further eliminated the possibility of false positive results due to plasmid contamination, confirming the validity of the HBV DNA identification in convalescent sera. In addition, the analysis suggested that these patients were most likely infected with the adw subtype of HBV which is the most common subtype in North America ( 18). Nested PCR with HBV core specific primers and Southernblot analysis of DNAs isolated from serum and plasma obtained at the same time point from an HBV-infected patient revealed that heparinization of blood interferes with the subsequent detection of HBV DNA by the PCR procedure described herein, while anticoagulation with EDTA or ACD does not (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Size differences between the HBV DNA fragments amplified from the sera and those from the plasmids further eliminated the possibility of false positive results due to plasmid contamination, confirming the validity of the HBV DNA identification in convalescent sera. In addition, the analysis suggested that these patients were most likely infected with the adw subtype of HBV which is the most common subtype in North America ( 18). Nested PCR with HBV core specific primers and Southernblot analysis of DNAs isolated from serum and plasma obtained at the same time point from an HBV-infected patient revealed that heparinization of blood interferes with the subsequent detection of HBV DNA by the PCR procedure described herein, while anticoagulation with EDTA or ACD does not (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There are at least three subgroups of HBV subtype adw differing in nucleotide sequence to an extent comparable with inter-subtypic variations. Courouce-Pauty et al (1983) have reported four subgroups of HBsAg subtype ayw, distinguishable by monospecific antibody, which they designated aywl, ayw2, ayw3 and ayw~. In addition, they recognized two subgroups of HBsAg subtype adw that they called adw 2 and adw~.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the four major subtypes of HBsAg, adw, adr, ayw and ayr, are generated, and they have been proposed to represent the phenotypic expression of the four major genotypes of HBV (Le Bouvier et al, 1972). HBsAg subtypes show distinct geographical distributions (Courouce-Pauty et al, 1983;Mazzur et al, 1974), and may provide historical information on the migration of ancestors carrying HBV of a particular subtype (Yamashita et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing of HBV/ayr, however, has not previously been accomplished, presumably because of the rarity and restricted geographical distribution of this subtype. HBV/ayr occurs in the Far East, accounting for 3-4~o of infections in Vietnam (Courouce-Pauty et al, 1983) and 0-5~ in Japan (Yamashita et al, 1975); it has not been found in Western countries or Africa where HBV strains are of either subtype adw or ayw. Determination of the entire nucleotide sequence of HBV/ayr has made it possible to correlate in detail the nucleotide sequence, as well as encoded amino acid sequences, with subtypic specificities of HBsAg and the combinations thereof.…”
Section: ~~`°~`~`~`~Cc`~c~`~c~°~~`~`~°~`~°°~`~`~ 3~oomentioning
confidence: 99%